Effect of Molasses and Organic Fertilizer in Soil fertility and Yield of Spinach in Khotang, Nepal - Pyakurel, Anish; Dahal, Bhishma Raj; Rijal, Swodesh (International Journal of Applied Sciences and Biotechnology, 2019)
A field experiment was conducted at Diktel Rupakot Majhuwagadhi Municipality of Khotang district during April 14 to May 28 of 2018 to evaluate the effect of molasses and organic fertilizer in soil fertility and yield of Spinach (Spinacia oleracea var 'patane local'). The effect of molasses and organic fertilizer in soil fertility and yield of spinach was evaluated by using RCBD (Randomized Complete Block Design) with five treatments and five replications. The five treatments were soil application of molasses, foliar application of molasses, molasses+organic fertilizer, organic fertilizer and controlled soil. The field was divided into 25 plots, each having an area of 1.2×1.2 m2 and distance between each plot was 0.5m. Spacing of 30×15 cm2 was maintained. The mean comparison was done through Duncan Multiple Range Test (DMRT). Molasses+organic fertilizer had highly significant result in soil organic carbon content (SOC), nitrogen, potassium, soil PH and yield of Spinach. Higher soil organic carbon (4.51%), nitrogen (0.24%), potassium (557.80 mg/kg) and yield (3.08kg) was obtained at molasses+organic fertilizer whereas soil application of molasses had significantly low PH (5.54). Poor soil fertility, lack of sustainable soil management, lack of chemical fertilizers was problems for declining crop productivity in Khotang district. The experiment suggests that, farmers could be benefitted by application of molasses and organic fertilizer as it improves soil fertility and increases the yield of spinach.Int. J. Appl. Sci. Biotechnol. Vol 7(1): 49-53